Switch to tenecteplase for intravenous thrombolysis in stroke patients: experience from a German high-volume stroke center - Alexander Sekita; Gabriela Siedler; Jochen A. Sembill; Manuel Schmidt; Ludwig Singer; Bernd Kallmuenzer; Lena Mers; Anna Bogdanova; Stefan Schwab; Stefan T. Gerner (Neurological Research and Practice)
Abstract Background Tenecteplase (TNK) offers promising efficacy and safety data for intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) and pharmacological advantages over alteplase (rt-PA), justifying its gradual adoption as primary thrombolytic agent. At our tertiary care center, we transitioned from rt-PA to TNK, providing valuable real-world insights into this process, including its use beyond the 4.5-hour time window. Methods We retrospectively analyzed our stroke registry to compare clinical and procedural data from AIS patients treated with rt-PA (up to 6 months before transition) and those treated with TNK (up to 6 months after transition, starting June 2024). Primary endpoints included treatment metrics, such as door-to-needle (DTN), door-to-imaging (DTI), imaging-to-needle (ITN), door-to-groin and door-to-recanalization times. Safety outcomes comprised rate of any intracranial hemorrhage (ICH), symptomatic ICH (sICH), parenchymatous hematoma type 2 (PH 2) and post-thrombolysis angioedema. A semiquantitative questionnaire evaluated satisfaction with TNK and changes in lysis behavior among nurses and physicians 3 months post-implementation. Results During the twelve-month period (December 1, 2023 - November 30, 2024), 276 patients underwent IVT. Median DTN times were significantly shorter with TNK (n = 138) compared to rt-PA (n = 138) (TNK 27 min [IQR 19–39] vs. rt-PA 34 min [IQR 25–62]; p = 0.011). No significant differences were observed in safety outcomes, including any ICH (TNK 9% vs. rt-PA 6%; p = 0.30), sICH (2% vs. 1%; p = 0.31), PH 2 rates (1% in both groups), or angioedema (3% vs. 1%; p = 0.18). Staff satisfaction with TNK was high, citing advantages in preparation, administration, and time efficiency. Importantly, no changes in lysis behavior were reported following the transition. Conclusions Transitioning to TNK in routine practice at a tertiary care center seems feasible with reduced ITN and consequently DTN times. Functional outcomes at discharge were comparable without significant difference in the rate of (s)ICH. Overall, the transition to TNK was well-received by medical staff, highlighting TNK’s practical advantages in acute stroke care. Trial registration N.A.